Performance of NAA, 2iP, BAP and TDZ on Callus Multiplication, Shoots Initiation and Growth for Efficient Plant Regeneration System in Chrysanthemum (Chrysanthemum morifolium Ramat.) - Rinaldi Sjahril; Feranita Haring; Muhammad Riadi; Muhammad Danial Rahim; Raham Sher Khan; Arjunayanti Amir; Trisnawaty A. R. (Hasanuddin University, 2016)
Three series of plant growth regulators experiments in Chrysanthemum tissue culture, each arranged in completely randomized design (CRD), were studied to formulate efficient plant regeneration system for developing Chrysanthemum plant cell engineering. In the first experiment, 100 mg callus were cultured in liquid Murashige and Skoog (MS) medium supplemented with different combinations of NAA and BAP concentrations treatments. After 30 days of culture, heaviest callus (1.55 g) was obtained in NAA (1.0 mg L-1) + BAP (0.5 mg L-1). Consequently, shoot regeneration experiment with different kinds and concentrations of auxin, i.e. NAA and 2iP were each combined with different concentrations of cytokine BAP. Callus grown on solid MS medium supplemented with both NAA and BAP at 0.5 mg L-1 showed fastest shoot initiation (30 days), largest number of shoots (5 shoots), longest shoot length (2.88 cm). While combination of 2iP (0.5 mg L-1) and BAP (2.0 mg L-1) also produced same response on shoot initiation but shorter (1.88 cm) and only one shoot. Largest number of shoots (3 shoots) was obtained in treatment BAP (0.5 mg L-1) without 2iP, although shoot initiation was slower (39 days) with shorter length (1 cm). In a separate experiment, effect of single treatment of potential synthetic cytokine for shoot regeneration, Thidiazuron (TDZ), at different concentrations was examined. However, callus grown on TDZ incorporated medium did not produce any shoots and changed from green to brown at end of study (90 days). It was assumed that TDZ inhibited formation of shoots in Chrysanthemum callus culture.